1992
DOI: 10.1115/1.2910053
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Uniform-Shear Flow Past a Circular Cylinder

Abstract: Extensive laboratory experiments were carried out to investigate the uniform-shear flow approaching a circular cylinder. The aim was to present the Strouhal number (St)-Reynolds number (Re) diagrams over a broad range of the shear parameter K (0 < K < 0.25) and at higher values of Re (600 < Re < 1600). An image processing technique, in conjunction with flow visualization studies, was used to secure more quantitative depictions of vortex shedding from the cylinder. The Strouhal number increases with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
51
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 7 publications
13
51
3
Order By: Relevance
“…For the square cylinder case, Ayukawa et al [9] and Hwang and Sue [10] reported positive mean lift coefficient (lift force acting from low velocity side to high velocity side), whereas Cheng et al [13,14] and Lankadasu and Vengadesan [15,16] reported negative mean lift coefficient. For the circular cylinder case, Kiya et al [18] and Kwon et al [19] reported positive mean lift coefficient whereas others reported negative mean lift coefficient. The reason for the above discrepancy among the reported mean lift coefficient is attributed to the number of parameters necessary viz, Reynolds number, blockage ratio, three-dimensionality effect, geometry and magnitude of the shear or combinations of any of these.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the square cylinder case, Ayukawa et al [9] and Hwang and Sue [10] reported positive mean lift coefficient (lift force acting from low velocity side to high velocity side), whereas Cheng et al [13,14] and Lankadasu and Vengadesan [15,16] reported negative mean lift coefficient. For the circular cylinder case, Kiya et al [18] and Kwon et al [19] reported positive mean lift coefficient whereas others reported negative mean lift coefficient. The reason for the above discrepancy among the reported mean lift coefficient is attributed to the number of parameters necessary viz, Reynolds number, blockage ratio, three-dimensionality effect, geometry and magnitude of the shear or combinations of any of these.…”
Section: Introductionmentioning
confidence: 96%
“…As a starting point, linear shear flow past a square cylinder [9][10][11][12][13][14][15][16] as well as a circular cylinder [17][18][19][20][21][22][23] has been studied. Except experimental results of Kiya et al [18] and 1116 A. LANKADASU AND S. VENGADESAN Kwon et al [19], all others reported that Strouhal number either decreases or remains constant and the mean drag coefficient decreases with increasing shear parameter. However, there is a disagreement on the direction and in the magnitude of the mean lift coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The case of a fixed circular cylinder placed in planar shear flow has been addressed experimentally Kwon, Sung & Hyun 1992;Sumner & Akosile 2003;Cao et al 2007) and numerically (Jordan & Fromm 1972;Yoshino & Hayashi 1984;Chew, Luo & Cheng 1997;Lei, Cheng & Kavanagh 2000;Kang 2006;Cao et al 2010). These prior studies, which mainly focused on linear shear, quantified the evolution of the vortex shedding frequency and time-averaged fluid forces as functions of the shear parameter (β), defined as the inflow velocity gradient normalized by the cylinder diameter and the oncoming flow velocity at the centre of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high quality of many of these experimental and numerical studies, some controversial issues remain unresolved [18,13]. Kiya et al [14], Tamura et al [25], Yoshino and Hayashi [31] and Kwon et al [17] claim that the Strouhal number St D = f D/U c increases with the shear rate. On the other hand, Lei et al [18], Sumner and Akosile [24], Vitola [28] and Kang [13] state that the Strouhal number decreases with the shear.…”
Section: Introductionmentioning
confidence: 98%